Novel heterozygous dysfibrinogenemia, Sumida (AαC472S), showed markedly impaired lateral aggregation of protofibrils and mildly lower functional fibrinogen levels. Issue 4 (April 2015) - Ikeda, Minami; Arai, Shinpei; Mukai, Saki; Takezawa, Yuka; Terasawa, Fumiko; Okumura, Nobuo
Abstract Introduction We encountered a 6-year-old girl with systemic lupus erythematosus. Although no bleeding or thrombotic tendency was detected, routine coagulation screening tests revealed slightly lower plasma fibrinogen levels, as determined by functional and antigenic measurements (functional/antigenic ratio = 0.857), suggesting hypodysfibrinogenemia. Materials and methods DNA sequence and functional analyses were performed on purified plasma fibrinogen, and recombinant variant fibrinogen was synthesized in Chinese hamster ovary cells based on the results obtained. Results DNA sequencing revealed a heterozygous AαC472S substitution (mature protein residue number) in the αC-domain. AαC472S fibrinogen indicated the presence of additional disulfide-bonded molecules, and markedly impaired lateral aggregation of protofibrils in spite of slightly lower functional plasma fibrinogen levels. Scanning electron microscopic observations showed a thin fiber fibrin clot, and t-PA and plasminogen-mediated clot lysis was similar to that of a normal control. Recombinant variant fibrinogen-producing cells demonstrated that destruction of the Aα442C-472C disulfide bond did not prevent the synthesis or secretion of fibrinogen, whereas the variant Aα chain of the secreted protein was degraded faster than that of the normal control. Conclusion Our results suggest that AαC472S fibrinogen may cause dysfibrinogenemia, but not hypofibrinogenemia. The destruction and steric hindrance of the αC-domain of variant fibrinogen led to the impaired lateral aggregation of protofibrils and t-PA and plasminogen-mediated fibrinolysis, as well as several previously reported variants located in the αC-domain, and demonstrated the presence of disulfide-bonded molecules.